To study the clinical profile of children with pleural effusion at a Tertiary Care Center in North India: A prospective study - Mehta, Poonam; Rathod, Kamleshkumar G; Bhalla, Kapil; Nanda, Sanjiv (Indian Journal of Child Health, 2017)
Introduction: Pleural effusion is the most common manifestation of pleural disorders and is mostly secondary to bacterial infections in children. Aims and Objectives: The primary objective was to study the clinical presentation of pleural effusion in hospitalized children. The secondary objective was to establish the etiology. Methods: A prospective observational study conducted from April 2014 to September 2015. Children >1 month and